The problem of duality of the personal and the transpersonal in the ethnopsychology of Armenians - Demirtshyan, MOVSES (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
In the absence of statehood, it is culture that becomes a system of means and forms of organizing the life of an individual and society, therefore, it can be described as a «project or program of life», in which all important events are identified, their time frames and ways of implementation are indicated. Since the absence of statehood in the history of the Armenian people periodically made impossible to organize the life of the whole society according to the same principles and norms, this function was assumed by culture. However, it could not claim such universality and obligation, which is possible under the conditions of a state by the laws and national ideology.Consequently, culture could organize a person's life not in the forms of a large «we» (nation or society), but in small forms of transpersonal being - a family, a clan, a community. Since they belong to the public sphere, in this way ethnic culture provided self-expression and self-affirmation of the individual in public relations.The transpersonal is also a natural continuation of the personal, therefore, small «we» - family, clan, community, etc. are natural forms of transpersonal existence, formed in the Armenian culture. Since the natural development of the personality at a certain stage presupposes the expression of the social essence of a person, the adaptation and socialization of the personality takes place through these forms of transpersonal existence in the Armenian culture. At the same time, it should be mentioned that the conditions and opportunities for the formation and expression of the big «we» - the nation and society - are provided by the state.The long lasting absence of the state in the history of the Armenian people led to the fact that historically the transpersonal was limited to small forms of expression that had and still have a pronounced ethno-cultural character. Along with the lack of statehood, culture proved its viability and performed an ethno-protective function, strengthening itself in the consciousness of Armenians as a guarantee of the spiritual existence and development of the people.Despite the fact that small forms of the transpersonal are public spheres of personality expression, they in fact cannot completely replace the system of social relations and from this point of view can be characterized as simulacra, since they are imitations of social life, that is, symbols of what is not real. This does not diminish their reality, on the contrary - it is precisely the relations of families, clans, clans, friends and communities that form the social reality of the Armenian society, especially if we take into consideration that these relations have their continuation in the spheres of economy and politics, creating a clan economy and clan politics.Thus, we can conclude that there are three levels of personal expression in the ethno-psychology of Armenians: «I», small «we» and big «we». The long absence of statehood, life in a foreign cultural environment and the constant threat of expulsion and destruction left unfinished the processes of the formation of large forms of the transpersonal - the nation and society, and at the same time contributed to the fact that Armenians for survival relied on their «I» and small «we» - the family, the clan, the friends and the community. Due to the social reality they created it became possible for each individual to implement a life program - to get an education, a work, create a family, achieve well-being, etc.
Keywords: ethno-culture; ethno-psychology; transpersonal; statehood; nation; homeland; clan; community